INTEGRASI KEGIATAN PENDIDIKAN AGAMA ISLAM DALAM TRAUMA HEALING PADA ANAK KORBAN BANJIR DI MEUNASAH MANCANG ACEH - Ahmad Aziz Mubaroq; Hilda Ainissyifa; Fiqra M Nazib (STKIP Pesisir Selatan, 2026)
Objective: This study aims to examine the implementation of Islamic Religious Education (PAI) activities within trauma healing programs for children affected by the 2025 flash flood disaster in Meunasah Mancang Village, Pidie Jaya, Aceh. Methods: A qualitative research approach with a case study design was applied. Data were obtained through participatory observation, in-depth interviews, and documentation involving children, teachers, parents, volunteers, and community stakeholders. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Results: The findings reveal that PAI-based interventions such as Quran recitation, collective prayer, dhikr practices, Islamic educational games, and prophetic storytelling significantly contribute to reducing children’s anxiety levels, improving emotional stability, and restoring their sense of security after the disaster. Furthermore, the involvement of volunteers strengthens social bonding and supports the psychosocial recovery process. Novelty: This study emphasizes a context-based integration of Islamic Religious Education into trauma healing practices within disaster-affected religious communities, offering an applicable and culturally responsive model for child psychological recovery.